2021
DOI: 10.4103/ija.ija_417_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supra-inguinal fascia iliaca versus pericapsular nerve block for ease of positioning during spinal anaesthesia

Abstract: Background and Aims: Regional analgesic techniques such as supra-inguinal fascia-iliaca compartment block (S-FICB) and pericapsular nerve group (PENG) block have been found to be effective in providing good pain relief in hip-fracture patients. However, comparative studies between PENG and S-FICB are lacking. The aim of this study was to compare the analgesic efficacy of S-FICB and PENG block and assess their efficacy in optimal patient positioning for spinal anaesthesia. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…Based on the Cochrane risk of the bias assessment tool, the quality of the included studies ranged from low to high quality with seven studies of low quality [15][16][17][18][19][20][21]; two of moderate quality [22,23]; and six high-quality studies [24][25][26][27][28][29]. Risk of bias graph and summary of quality assessment domains of included studies are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Cochrane risk of the bias assessment tool, the quality of the included studies ranged from low to high quality with seven studies of low quality [15][16][17][18][19][20][21]; two of moderate quality [22,23]; and six high-quality studies [24][25][26][27][28][29]. Risk of bias graph and summary of quality assessment domains of included studies are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…An RCT comparing FNB to FICB found equivalent levels of pain control with either block but more rapid relief with FNB [44]. There have been 3 randomized controlled trials comparing PENG to either FNB or FICB for operative analgesia in total hip arthroplasty, with two showing less short-term pain and better preservation of motor function with PENG [45,46]. However, all showed no significant difference in post-operative pain at 24 h [45][46][47].…”
Section: Lower Extremitymentioning
confidence: 99%
“…10,[16][17][18][19] A perioperative study showed the PENG block to be superior to suprainguinal FICB prior to patient positioning for spinal anaesthesia. 16 The objective of the present study was to confirm the feasibility of the PENG block in everyday ED practice and to compare the safety and effectiveness of the PENG block to FB for patients with hip fracture in the ED. We hypothesised that it is safe and effective for emergency medicine clinicians to provide the PENG block for patients presenting to ED with a hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…15 Comparative literature for the PENG block is limited to the investigation of perioperative use of the technique by anaesthetists. 10,[16][17][18][19] A perioperative study showed the PENG block to be superior to suprainguinal FICB prior to patient positioning for spinal anaesthesia. 16 The objective of the present study was to confirm the feasibility of the PENG block in everyday ED practice and to compare the safety and effectiveness of the PENG block to FB for patients with hip fracture in the ED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation